ANALISIS FAKTOR KEBERHASILAN PROGRAM KESEHATAN JIWA DI UPTD PUSKESMAS GUNUNG TUA KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL TAHUN 2022 - Irwandi, Syahlis; Harahap, Syarifah (Deli Medical and Health Science Journal, 2024)
The Gunung Tua number one medical institution is one of the fitness centers that has not succeeded in reaching the goal for the ODGJ indicator of getting offerings in step with 2021 standards with an achievement of 65.38%. The PIS-PK effects of human beings with PLWI taking everyday medicinal drug were 64.10 (%) with a healthy family index (IKS) of zero.14.This form of research is blend-method which objectives to investigate the success elements of enforcing a intellectual health program on the UPTD Gunung Tua health facility, Panyabungan District, Mandailing Natal Regency. Retrieval_ of informants using purposive sampling method as many as 10 human beings. statistics collection changed into performed using interviews and report assessment. Triangulation became finished inside the shape of triangulation of sources, methods and statistics.The results showed that the achievement of the intellectual fitness application had no longer reached the countrywide target of sixty five.38%. The success of a mental fitness software can not be achieved beginning from the context, enter, system, product which might be interconnected with each other.facilities and infrastructure within the mental fitness program ought to be completed with the resource of the health facility with the aid of coordinating with the fitness workplace so that during wearing out the usual of products can be met.